Chronic pancreatitis: Risk Factors and Clinico-Radiological Profile (Nepal Medical College Journal, 2021)
Chronic pancreatitis is a disease condition characterized by progressive inflammation and fibrosis of pancreas. It manifests with pain abdomen, endocrine and exocrine dysfunction. Diagnosis is often difficult and is relied mostly on radiological examination. The aim of this study was to identify associated risk factors and correlate the clinical presentation with various radiological changes of the pancreas.We conducted a prospective hospital based observational study in patients presenting with abdominal pain and evaluated the etiology, clinical presentation and radiological changes of pancreas among 68 chronic pancreatitis patients visiting Gastroenterology Unit, Department of Medicine, National Academy of Medical Sciences, Bir Hospital during 1 year period (November 2019 to October 2020 AD). The results showed mean age of 35.75 ± 11.43 years with predominant male patients (76.4%). Pain abdomen was present in all patients with mean duration of 16.5 months, followed by diabetes in 27.9%. Alcohol was the major risk (n=42, 61.8%) and no cause was identified in 22 (32.3%) patients. Pancreatic parenchymal calcification in 65 (95.6%), duct dilation in 61 (89.7%) and gland atrophy in 39 (57.3%) were major structural changes detected in computed tomography scan, more reliably than ultrasonography. One third of patients had diabetes mellitus, which was significantly higher in female (63.2%) and had major radiological changes of chronic pancreatitis at diagnosis. Alcohol was the common risk of chronic pancreatitis. Structural changes suggestive of disease was demonstrated better by computed tomography.